SOCIAL VARIATION IN REGIOLECT (Philological Studies, 2020)
The subject of the research is variation of the frequency of phonetic and lexical regional-specific speech features under the influence of such social factors as gender, age, place of birth and education. The regiolect is the general features of speech of a rather vast region without dividing them into urban and rural; the research includes the Perm regiolect of the Russian language. The material for the study is spontaneous monologues received from residents of the Perm Region. This material demonstrates that phonetic and lexical regional features depend on the same social factors – “place of birth” and “age”. The frequency of i particular phonetic features is determined by the influence of various social factors; lexical regionalisms are more common among residents of non-central cities of the Perm Region and informants of the older generation.
Keywords: sociolinguistics; regiolect; phonetic features; lexical features; social variation; social factors